Light engineering in aquaculture: physiological responses of Takifugu rubripes larvae to controlled LED irradiance - Xin Li; Songtao Liu; Yafang Liu; Pingping Wei; Yanling Wu; Yingying Fang; Fei Sun; Ying Liu; Yumeng Wu; He Ma (Frontiers in Marine Science, 2026)
Introduction While indoor aquaculture has expanded globally, optimal lighting strategies for fish growth remain understudied. This study aims to establish optimal LED protocols for indoor-reared Takifugu rubripes larvae. Methods T. rubripes larvae were maintained at 50, 250, 500, and 750 mW/m 2 (i50, i250, i500, i750) from hatching through 30 DPH. Growth, gene expression, and enzyme activities were measured. Results Positive growth effects were observed at i250 and i500 within 14–17 DPH, while i50 caused complete mortality after 21 DPH. At 20 DPH, i500 upregulated IGF-1 and BMP2 expression, whereas i50 downregulated BMP4 and SOX9. i50 elevated CTSF, IGM, and HSP70, indicating stress. LPS activity was highest in i250 at 15 DPH, while LDH was lowest in i50. From 10–20 DPH, AKP and ACP were consistently lower in i50. During 5–20 DPH, SOD was suppressed in i750, while T-AOC increased in i250. Discussion Light conditions critically modulate enzymatic activity and early growth in T. rubripes larvae, though underlying mechanisms require further investigation.

Bioactive electrospun membrane with DHBA/Zn-MOF for enhancing neurovascular coupling in diabetic wound healing - Manjuan Li; Peng Hua; Linsa Zhou; Lexuan Fang; Pingping Ma; Zixuan Wang; Shicui Jiang; Qiang Zhou; Gaowen Li; Xudong Zheng; Chi Zhang; Litai Jin; et al. (Chemical Engineering Journal, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

A robust estimation method for canopy chlorophyll content based on FOD and hierarchical weighting combination models - Jie Zhang; Xiaoyu Song; Yuanyuan Ma; Laigang Wang; Liang Sun; Li Li; Heguang Sun; Chunkai Zheng; Pingping Li; Xia Jing; Guijun Yang; Chunjiang Zhao (European Journal of Agronomy, 2026)

A spatial ZVI strategy boosts digestion performance and ammonium recovery through in-situ conductive mineral formation - Yuqi Gong; Xiaocheng Guo; Pingping Huang; Yangzhao Guo; Yikun Jiang; Fengzhi Jiang; Zhigang Ma; Siping Ji (Journal of Water Process Engineering, 2026)

Microbial generalists and specialists in permafrost demonstrate disparate responses to extreme environments - Chengzhi Mao; Pingping Xu; Ramiro Logares; Bing Ma; Jianchuan Li; Rong Tang; Jiayuan Wang; Xiaosong Wang; Jinglan Wang; Yitong Wang; Yuxiu Chen; Lingyun Chen (Journal of Environmental Management, 2026)

Branch-connected construction of shamrock-shaped giant molecule acceptors enables efficient organic solar cells through optimized molecular architecture - Shanshan Qin; Kangqiao Ma; Jiajia Xi; Fengzhi Wang; Pingping Xi; Hong Huang; Zhenyu Chen; Tao Zhang; Kang Wang; Deping Qian (Chemical Engineering Journal, 2026)

RFAGB model: A new machine learning model for microplastic inversion based on remotely sensed data in Bohai Sea - Ao Shen; Yongzheng Ma; Yuan Li; Pingping Hong; Zhiguang Niu; Ying Zhang; Jingen Xiao; Dianjun Zhang (Water Research, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Curcumin alleviates ovarian hyperstimulation syndrome in the rat model via inhibiting the nuclear factor kappa B/hypoxia-inducible factor-1α signaling pathway - Lilan Sun; Xiumei Zhuo; Dandan Qi; Hao Ma; Fanhua Kong; Pingping Sun; Yan Zhang; Peng Xue; Huagang Ma (Histochemistry and Cell Biology, 2025)

Prediction of potential habitats of three Coptis species under climate change provides insights on their resource protection and cultivation across China - Pingping Lu; Jieru Chen; Hongting Liu; Xinyue Zhu; Zichun Ma; Xue Huang; Wei Zhang; Hezhong Jiang; Hai Liao; Jiayu Zhou (Environmental Monitoring and Assessment, 2025)

Nitrogen-doped porous carbon derived from MIL-88-NH2 precursors for sulfur cathode of Na S batteries - Mei Yang; Qiuyang Ma; Hengli He; Jiaqi Zhang; Shanshan Zhu; Xuanming Chang; Luzhou Zhang; Pingping Zhou; Zhong Wu; Guilin Zhuang; Zhen Fang (Chemical Engineering Journal, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Soil microbial diversity and physicochemical properties: key drivers of yield and quality in wine terroir - Haoyu Wang; Jixin Dong; Guangzheng Ma; Pingping Yang; Rui Wang; Yaqi Wang (Rhizosphere, 2025)

Synergistic efficiency in pollution and carbon reduction: Measurement, evolution, and pathways in Chinese cities - Pingping Ma; Ming Zhang; Wenqi Wu; Bangzhu Zhu (Environmental Impact Assessment Review, 2025)

Removal of dissolved arsenic from deep seawater around hydrothermal vents and seamounts - Yuanchen Li; Guangyong Bo; Yihua Cai; Kan Zhang; Kuanbo Zhou; Pingping Zhang; Chenjing Yang; Tianyu Chen; Minhan Dai; Jian Ma; Zhimian Cao (Earth and Planetary Science Letters, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

An efficient, robust, and affordable photothermal membrane using polyvinyl alcohol encapsulated MXene/non-woven fibers for solar desalination/sewage purification - Ye Cao; Pingping Gong; Peng Yu; Yijing Wang; Zhenli Zuo; Changyuan Pan; Xinbing Wang; Peng Zhong; Xiaohua Ma (Chemical Engineering Journal, 2025)

Extracellular vesicles derived from “serum and glucose” deprived HUCMSCs promoted skin wound healing through enhanced angiogenesis - Xiaopeng Wu; Pingping Yuan; Na Wei; Chaoqun Ma; Mingdi Fu; Wei Wu (Molecular and Cellular Biochemistry, 2025)

Influence of topography on the fragmentation and mobility of landslides - Zhaodong Li; Jian Guo; Tonglu Li; Ping Li; Xuetong Ma; Mengmeng Zhang; Enxian Jia; Pingping Xu (Bulletin of Engineering Geology and the Environment, 2025)

Inversion of biophysical parameters of potato based on an active learning pool-based sampling strategy - Yuanyuan Ma; Xiaoyu Song; Jie Zhang; Di Pan; Haikuan Feng; Guijun Yang; Chunxia Qiu; Heguang Sun; Chunkai Zheng; Pingping Li (International Journal of Remote Sensing, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Analysis of Tidal Current Energy Potential in the Major Channels of the Bohai Strait Based on Delft3D - Pengcheng Ma; Hongyuan Shi; Huaiyuan Xue; Pingping Li; Yongkang Sun (Journal of Ocean University of China, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Identification and Expression Profiles of Auxin-Related Gene Families Involved in Fiber Development in Jute (Corchorus capsularis) - Shaolian Jiang; Huawei Wei; Mengxin Huang; Lingling Zhuang; Jinping Huang; Haixiong Ma; Pingping Fang; Aifen Tao; Jianmin Qi; Jiantang Xu; Liwu Zhang (Tropical Plant Biology, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

In-situ synthesis of ZIF-8 on magnetic pineapple leaf biochar as an efficient and reusable adsorbent for methylene blue removal from wastewater - Xiaoxiao Ma; Yutong Li; Yile Du; Shuangli Chen; Yunfan Bai; Lin Li; Chuhua Qi; Pingping Wu; Sijing Zhang (Environmental Science and Pollution Research, 2024)

Cd-contaminated soil remediation using MgFe2O4/chitosan carbon aerogel beads - Yutong Li; Xiaoxiao Ma; Yile Du; Shuangli Chen; Pingping Wu; Sijing Zhang (Journal of Environmental Chemical Engineering, 2024)

An inversion model of microplastics abundance based on satellite remote sensing: a case study in the Bohai Sea - Pingping Hong; Jingen Xiao; Hongtao Liu; Zhiguang Niu; Yini Ma; Qing Wang; Dianjun Zhang; Yongzheng Ma (Science of The Total Environment, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Rasterizing CO2 emissions and characterizing their trends via an enhanced population-light index at multiple scales in China during 2013–2019 - Bin Guo; Tingting Xie; Wencai Zhang; Haojie Wu; Dingming Zhang; Xiaowei Zhu; Xuying Ma; Min Wu; Pingping Luo (Science of The Total Environment, 2023)

High titer (>200 g/L) lactic acid production from undetoxified pretreated corn stover - Yuwei Zhang; Zhaoxian Xu; Minrui Lu; Xingwang Ma; Sitong Chen; Yanchen Wang; Wenyuan Shen; Pingping Li; Mingjie Jin (Bioresource Technology, 2023)

Analysis of the evolution of the Yellow River Delta coastline and the response of the tidal current field - Lili Zhang; Hongyuan Shi; Hao Xing; Pingping Li; Pengcheng Ma (Frontiers in Marine Science, 2023)
The coastline of the Yellow River Delta has undergone continual alterations due to both natural forces and human activity. Studying these changes is crucial for promoting economic growth and preserving the region’s ecological balance. Based on imagery captured by the Landsat5 and Landsat8 satellites, this study uses statistical data from the Digital Shoreline Analysis System (DSAS), including Net Shoreline Movement (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR), to analyze the changes in the Yellow River Delta coastline from 2009 to 2019. This being the case, a hydrodynamic model under different shoreline conditions was established using Delft3D to compare and analyze the impact of shoreline changes on the tidal current field. From 2009 to 2019, the coastline in the study area exhibited an average movement distance of 1285m (NSM) and an annual change rate of 127.7m/a (LRR). The average increase in the area of the current estuary was 7.68km 2 /a, while the average decrease in the area of the old estuary was 4.91km 2 /a. Shoreline evolution is primarily influenced by the influx of water and sediment into the ocean. Following the implementation of water and sediment regulation, the existing estuary’s shoreline experienced a rapid initial accumulation of silt, which subsequently decelerated over time. Conversely, the former estuary has consistently undergone erosion. The greater the change in shoreline, the closer to the coast, and the greater the change in the tide. From 2009 to 2019, flow velocity and direction in the Yellow River Delta generally showed a decreasing trend, with changes ranging from 0.34% to 25.94%. The residual flow velocity near the current estuary gradually increased by about 2cm/s, while that near the abandoned old estuary gradually decreased by about 1cm/s, with no significant changes offshore. The sediment transported by the Yellow River is deposited at the current estuary, causing the coastline to move northeastward. In the abandoned estuary, there is erosion, causing the coastline to retreat.

The transcription factor NtERF13a enhances abiotic stress tolerance and phenylpropanoid compounds biosynthesis in tobacco - Zhong Wang; Jinchu Yang; Qian Gao; Shun He; Yongming Xu; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Xin Xu; Lanxin Ma; Zhan Zhang; Yongfeng Yang; et al. (Plant Science, 2023)

Mediating and spatial spillover effects of public participation in environmental pollution governance mediated via traditional and new media - Pingping Ma; Yan Song; Ming Zhang (Journal of Environmental Management, 2023)

Cost and life cycle analysis for deep CO2 emissions reduction of steelmaking: Blast furnace-basic oxygen furnace and electric arc furnace technologies - Guiyan Zang; Pingping Sun; Amgad Elgowainy; Pallavi Bobba; Colin McMillan; Ookie Ma; Kara Podkaminer; Neha Rustagi; Marc Melaina; Mariya Koleva (International Journal of Greenhouse Gas Control, 2023)

How does environmental tax affect enterprises’ total factor productivity? Evidence from the reform of environmental fee-to-tax in China - Longke Wang; Pingping Ma; Yan Song; Ming Zhang (Journal of Cleaner Production, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Effects of LED spectrum on circadian rhythmic expression of clock genes and Aanat2 in the brain of juvenile European seabass (Dicentrarchus labrax) - He Ma; Songtao Liu; Pingping Wei; Fan Fei; Jilong Ren; Mingyun Dai; Zhen Ma; Ying Liu (Frontiers in Marine Science, 2023)
The circadian rhythm is a physiological phenomenon that occurs in various organisms with a cycle of about 24 hours. Light is one of the important environmental factors affecting biological rhythm. To clarify whether a shift in light spectrum can influence the circadian expression in fish brain, a total of 175 European seabasses [body weight: 32.5 ± 0.71) g; body length: (13.78 ± 0.35) cm] were exposed to white light (WL), red light (RL), yellow light (YL), green light (GL) or blue light (BL). After 50 days of exposure, circadian expressions of four core clock genes ( Clock, Bmal1, Per2, Cry1 ) and Aanat2 gene in brain were examined. The results showed that the temporal expression patterns of positive clock gens ( Clock and Bmal1 ) showed increases during the scotophase and decreases during the photophase, with peaks near the middle of the darkness. Clock gene expression showed a stable circadian rhythm (R 2 = 0.578-0.824, P =0.000- 0.027) in all light groups while Bmal1 showed circadian rhythm in WL, GL and RL, not in BL and YL. Daily expression patterns of the negative clock genes oscillated in the opposite phase from the positive clock genes, showing increasing mRNA levels during the light, decreases during the dark, and peaks near the shift from night to day, except Per2 in RL and Cry1 in BL. Compared with WL, the acrophases of Clock and Bmal1 were delayed under all light treatments (BL: + 3.7h, +6.73h; RL: +2.4h,+1.35h; YL: + 4.94h, 2.00h; GL: +0.05, +0.16h). Cry1 showed advanced acrophase under all light treatments (BL: -10.74 h, GL: -3.81 h, RL: -3.93 h, YL: -7.56 h) but Per2 showed delayed acrophase in all light treatments (GL: +0.86 h, RL: +10.35 h, YL: +9.62 h), except in BL (-0.43 h). The acrophase of Aanat2 was advanced by all monochromatic light, the Aanat2 level was significantly increased in RL compared with other light treatment. Therefore, the results indicate that RL may regulate the expression of Aanat2 gene by affecting the expression of clock gene in fish brain. Spectrum can affect the biological clock system of fish, and unreasonable spectrum may disturb the rhythm of gene expression of biological clock of fish. Under the irradiation of light spectrum, some clock genes still maintain obvious circadian oscillation, while the rhythm of some clock genes is not obvious and may be destroyed. Our findings suggest a primary role of light spectrum information to the fish brain circadian system.

Transcription factor NtWRKY33a modulates the biosynthesis of polyphenols by targeting NtMYB4 and NtHCT genes in tobacco - Zhong Wang; Lanxin Ma; Pingping Liu; Zhaopeng Luo; Zefeng Li; Mingzhu Wu; Xin Xu; Wenxuan Pu; Pingjun Huang; Jun Yang (Plant Science, 2023)

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

BiPO4-coated carbon microtube electrodes: preparation and characterization of their properties and electrocatalytic degradation of methylene blue - Wenli Qin; Zefei Chen; Xueya Liu; Xinyi Zhang; Manqing Ai; Pingping Zhang; Ying Ye; Zengling Ma (Environmental Science and Pollution Research, 2022)

Spatial Distribution and Assessment of the Human Health Risks of Heavy Metals in a Retired Pharmaceutical Industrial Area, Southwest China - Shiyu Wang; Zhaohui Ma; Guoren Yue; Haolan Wu; Pingping Wang; Ling Zhu; Cunzhen Liang; Chengcheng Xie; Shuo Wang; Wentao Jiao; Bendong Zou; Baoxian Liu (Bulletin of Environmental Contamination and Toxicology, 2022)

The genome of a mangrove plant, Avicennia marina, provides insights into adaptation to coastal intertidal habitats - Dongna Ma; Qiansu Ding; Zejun Guo; Chaoqun Xu; Pingping Liang; Zhizhu Zhao; Shiwei Song; Hai-Lei Zheng (Planta, 2022)

First Report on Large-Scale Phaeocystis globosa Bloom in the Southern Yellow Sea, China - Dongmei Li; Yue Xue; Qingshang Song; Fuxu Cui; Yujuan Ma; Mengmeng Tong; Pingping Shen (Frontiers in Marine Science, 2022)
From late November 2021, a large-scale Phaeocystis globosa bloom occurred for the first time in the southern Yellow Sea, covering an area of over 630 km 2 and lasting for nearly 40 days. Two investigations, combined with satellite remote sensing, were successively conducted on December 11 and 23, 2021 to study the bloom dynamics and impacts. During the bloom, the average temperature decreased from 11.8°C to 10.0°C and salinity increased slightly from 30.9 to 31.3. The pH remained consistently at 8.22, while dissolved oxygen and chlorophyll -a content decreased dramatically from 7.23 mg L -1 to 5.82 mg L -1 , 8.72 μg L -1 to 2.35 μg L -1 , respectively. The concentration of nitrate and silicate decreased moderately, whereas nitrite, ammonium and phosphate increased obviously, especially the ammonium content, elevated from 0.90 μmol L -1 to 1.39 μmol L -1 during two investigations. Meanwhile, the P. globosa colony densities varied between 10 colonies L -1 and 185 colonies L -1 , with a mean of 70.0 colonies L -1 on Dec. 11, and decreased dramatically to an average of 1.46 colonies L -1 on Dec. 23. Similarly, single cells decreased from 3.6×10 6 cells L -1 to 1.05×10 6 cells L -1 accordingly. Moreover, diameter of the colonies varied from 0.5 cm to 2.0 cm, with an average diameter of 1.0 cm, and no colonies smaller than 0.5 cm was observed in the bloom. Correlation analysis indicated temperature and salinity related with the colony abundance positively (P<0.001) and negatively (P<0.05), respectively, and silicate and nitrite concentration showed significant positive effects on solitary cell density (P<0.05). No mortality of marine organisms was observed and the haemolytic activity of Phaeocystis samples was low, varying between 13.07 Hu L -1 and 19.22 Hu L -1 . Based on phylogenetic analysis, this P. globosa strain may represent a possible different ecotype which prefers low temperature and is less or nontoxicity.

Effects of controlled atmosphere on browning, redox metabolism and kernel quality of fresh in-hull walnut (Juglans regia L.) - Niu Ye; Pingping Zhang; Yifan Wang; Huiling Ma; Ting Zhang (Horticulture, Environment, and Biotechnology, 2021)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Perfluoroalkyl substances in the Lingang hybrid constructed wetland, Tianjin, China: occurrence, distribution characteristics, and ecological risks - Ziang Chen; Gengbo Ren; Xiaodong Ma; Ye Ding; Yunmin Hui; Pingping Qin; Zhuoqi Xu; Xiujun Gu; Fang Yuan; Yanhai Liu (Environmental Science and Pollution Research, 2020)

Mechano growth factor pretreatment yield mechanical stimuli induced cell stress responses in ligament fibroblasts of osteoarthritis via activating ATF-2 - Yu Ma; Yang Song; Linhao Li; Lili Dong; Chunli Wang; Pingping Wang; Li Yang (Biotechnology Letters, 2020)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

Joint Inversion of 1-D Magnetotelluric and Surface-Wave Dispersion Data with an Improved Multi-Objective Genetic Algorithm and Application to the Data of the Longmenshan Fault Zone - Pingping Wu; Handong Tan; Miao Peng; Huan Ma; Mao Wang (Pure and Applied Geophysics, 2018)

Increased Active Tumor Targeting by An αvβ3-Targeting and Cell-Penetrating Bifunctional Peptide-Mediated Dendrimer-Based Conjugate - Pengkai Ma; Huajun Yu; Xuemei Zhang; Hongjie Mu; Yongchao Chu; Ling Ni; Pingping Xing; Yiyun Wang; Kaoxiang Sun (Pharmaceutical Research, 2017)

Formation of melt pocket in mantle peridotite xenolith from western Qinling, Central China: Partial melting and metasomatism - Benxun Su; Hongfu Zhang; Patrick Asamoah Sakyi; Kezhang Qin; Pingping Liu; Jifeng Ying; Yanjie Tang; Sanjeewa P. K. Malaviarachchi; Yan Xiao; Xinmiao Zhao; Qian Mao; Yuguang Ma (Journal of Earth Science, 2010)